Human occupation of the Kimberley coast of northwest Australia 50, 000 years ago. (15th July 2022) - Norman, Kasih; Shipton, Ceri; O'Connor, Sue; Malanali, Wudugu; Collins, Peter; Wood, Rachel; Saktura, Wanchese M.; Roberts, Richard G.; Jacobs, Zenobia
Abstract: The peopling of Sahul (the combined landmass of New Guinea and Australia) is a topic of much debate. The Kimberley region of Western Australia holds many of Australia's oldest known archaeological sites. Here, we review the chronological and archaeological data available for the Kimberley from early Marine Isotope Stage 3 to the present, linking episodes of site establishment and the appearance of new technologies with periods of climatic and sea-level change. We report optical ages showing human occupation of Widgingarri 1, a rockshelter located on the Kimberley coast of northwest Australia, as early as 50, 000 years ago, when the site was located more than 100 km from the Late Pleistocene coastline. We also present the first detailed analysis of the stone artefacts, including flakes from ground stone axes, grinding stones and ground haematite recovered from the deepest excavated layer. The high proportion of flakes from ground axe production and resharpening in the earliest occupation phase emphasises the importance of this complex technology in the first peopling of northern Sahul. Artefact analyses indicate changes in settlement patterns through time, with an increase in mobility in the terminal Pleistocene and a shift to lower mobility during the late Holocene. The optical ages for Widgingarri 1 mean that the Kimberley now contains the greatest number of sites in Sahul with earliest occupation dated to more than 46, 000 years ago, overlapping with the time of initial occupation of sites in other regions across the continent. Highlights: Redating of Widgingarri 1 using OSL reveals occupation of the site began ∼50, 000 years ago. The Kimberley region now contains the most archaeological sites dated to this period in Sahul. Widgingarri 1 contains some of the oldest evidence for ground stone axe manufacture in Sahul. Kimberley-wide peopling and occupation patterns linked to periods of climate and sea level change. Updated Bayesian age models of oldest sites in Sahul show high degree of overlap in first occupation.